Recycling of polyethylene terephthalate bottles - Thomas, Sabu, editor. 391529; Rane, Ajay V., 1987- editor.; Kanny, Krishnan, editor.; Abitha V. K., editor.; Thomas, Martin George, editor. (Kidlington, Oxford ; Cambridge, MA : William Andrew, 2019)
Includes bibliographical and references